Influence of intravenous 10% amino acids infusion on serum albumin concentration in hypoalbuminemic dogs - Schneider, Sabrina; Hartmann, Katrin; Dörfelt, René (Frontiers in Veterinary Science, 2023)
Objective To evaluate the effect of parenteral amino acid application in hospitalized hypoalbuminemic dogs. Materials and methods Medical records of client-owned hypoalbuminemic dogs (albumin ≤ 25 g/L) were analyzed. Dogs receiving amino acids for only 1–2 days, receiving transfusions or surgery, or <6 months of age were excluded. Dogs were grouped as those receiving intravenous amino acids (AA, 80 dogs) over 3 days and longer, and those without additional amino acid treatment (CON, 78 dogs). Duration of hospitalization, albumin, and total protein concentrations were compared between groups by Mann–Whitney U test. Course of albumin and total protein concentration was evaluated by Friedman test and Dunn’s multiple comparison test. Significance was set to p ≤ 0.05. Results Dogs in group AA received 10% amino acid solution intravenously over median 4 days (3–11 days). No significant differences regarding survival and adverse effects were observed between groups. Dogs of group AA had significantly longer duration of hospitalization (median 8 days; 3–33 days) compared to group CON dogs (median 6 days, 3–24 days; p < 0.001). Initial albumin concentration was lower in group AA compared to CON (p < 0.001). This difference was no longer present on day 2 (p = 0.134). Conclusions and clinical relevance Intravenous application of 10% amino acid solution in hypoalbuminemic dogs can improve albumin concentration after 2 days, but does not influence outcome.